2022
DOI: 10.3389/fmars.2022.924556
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene to Holocene variations in marine productivity and terrestrial material delivery to the western South Atlantic

Abstract: Despite the increased number of paleoceanographic studies in the SW Atlantic in recent years, the mechanisms controlling marine productivity and terrestrial material delivery to the South Brazil Bight remain unresolved. Because of its wide continental shelf and abrupt change in coastline orientation, this region is under the influence of several environmental forcings, causing the region to have large variability in primary production. This study investigated terrestrial organic matter (OM) sources and marine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…We thus propose that the ACL in core GL-1090 traces changes in the Atlantic Forest in SE Brazil with lower (higher) ACL indicating expansion (retraction) of the forest. A previous record in the study area has suggested using ACL as a proxy for changes in the Atlantic Forest 53 . In order to further constrain the ACL as a tracer of vegetation (Atlantic Forest) changes, we compared our results with available pollen data from the Colônia crater in SE Brazil located only a few kilometers from the shoreline 30 .…”
Section: Discussionmentioning
confidence: 99%
“…We thus propose that the ACL in core GL-1090 traces changes in the Atlantic Forest in SE Brazil with lower (higher) ACL indicating expansion (retraction) of the forest. A previous record in the study area has suggested using ACL as a proxy for changes in the Atlantic Forest 53 . In order to further constrain the ACL as a tracer of vegetation (Atlantic Forest) changes, we compared our results with available pollen data from the Colônia crater in SE Brazil located only a few kilometers from the shoreline 30 .…”
Section: Discussionmentioning
confidence: 99%